Implementation of Project Based Learning Student Worksheets to Improve Students' Science Process Skills on Environmental Pollution in High Schools - Setiawan, R. Razak; Suwondo, Suwondo; Syafii, Wan (FKIP-Universitas Riau, 2021)
This study aims to determine the improvement of students' science process skills through the application of Project Based Learning based LKPD on environmental pollution material for Class X Senior High School. This research was conducted at MAN 1 Kuantan Singingi. The method used in research is development research (Research and Development). Sources of research data came from 25 students of class X IPA 3. Research design using one group pretest posttest only. Data collection obtained from the preetest and posttest results of the student's Science Process Skills instrument. The results showed that the students' science process skills experienced an increase in the posttest results, from 63.5 to 83.5 with a medium increase (N-Gain 0.54). From the research results, it can be concluded that LKPD based on project based learning can be used as a medium for learning biology in high school.